Impact Of Flexible Work Arrangements on Job Satisfaction Amonhg Women in Multinational Corporations with Special Reference to Chennai City - E, Divyalakshmi.; Devi, E. Brindha (Journal of Neonatal Surgery, 2025)
In the modern corporate landscape, achieving a sustainable work-life balance has become a central concern, particularly for women professionals. This study examines the impact of flexible work arrangements (FWAs) on job satisfaction among women employees in multinational corporations (MNCs) operating in Chennai, India. The research specifically investigates the influence of three major FWA componentsflexible working hours, work-from-home options, and compressed workweekson employee satisfaction. A descriptive research design and quantitative approach were adopted, utilizing a structured questionnaire administered to 125 randomly selected respondents. Data analysis included percentage analysis, exploratory factor analysis (EFA), and multiple linear regression using SPSS software. The findings reveal a strong and positive relationship between flexible work arrangements and job satisfaction. Among the independent variables, flexible working hours had the most significant impact, followed by work-from-home and compressed workweek options. The study underscores the importance of adopting inclusive and adaptable work models to foster greater satisfaction, engagement, and retention of women employees in MNCs. These insights provide actionable implications for HR managers and policymakers aiming to promote employee well-being and organizational effectiveness